2018
DOI: 10.30835/2413-7510.2018.152144
|View full text |Cite
|
Sign up to set email alerts
|

Grain quality of tetraploid wheat Triticum timopheevii (Zhuk.) Zhuk.

Abstract: The article is devoted to the comprehensive investigation of the quality parameters of tetraploid wheat (Triticum timopheevii) grain. Particular attention is paid to prospects of involving T. timopheevii in breeding programs as a resource of valuable quality and technology properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(7 reference statements)
3
1
0
Order By: Relevance
“…Both T. timopheevii and T. zhukovskyi revealed a very hard kernel texture (HI > 80, Table 1), comparable to that of durum wheat. These results agree with Relina et al [20] who classified the T. timopheevii kernels as hard-textured.…”
Section: Physical Kernel Traitssupporting
confidence: 92%
See 3 more Smart Citations
“…Both T. timopheevii and T. zhukovskyi revealed a very hard kernel texture (HI > 80, Table 1), comparable to that of durum wheat. These results agree with Relina et al [20] who classified the T. timopheevii kernels as hard-textured.…”
Section: Physical Kernel Traitssupporting
confidence: 92%
“…The TKW values of de-hulled kernels were very similar in the Caucasian wheats, and they resulted in almost half of those of T. durum (Table 1). The TKW values were comparable to those obtained from the ancient wheats einkorn, spelt and emmer [36], but they were lower than those observed as the mean of more than 50 T. timopheevii accessions by Mikò et al [37] and by Relina et al [20], who found TKW values ranging from 33 to 39 g. These differences could be due to the agronomic practices, growing environment and genotypes used in the different studies. Similarly, no differences were observed between T. timopheevii and T. zhukovskyi for the TW values, which resulted in being statistically lower (p ≤ 0.05) than those observed in durum wheat (Table 1).…”
Section: Physical Kernel Traitssupporting
confidence: 72%
See 2 more Smart Citations